2009
DOI: 10.1111/j.1525-1470.2009.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cutaneous Manifestations of Spinal Dysraphism from India

Abstract: Recognition of cutaneous markers of spinal dysraphism is important to prevent the morbidity associated with underlying spinal anomalies. To investigate the frequency and type of cutaneous stigmata in different forms of spinal dysraphism and to assess the role of ultrasonography and/or magnetic resonance imaging in diagnosing spinal dysraphism at two pediatric dermatology tertiary care centers. Over a 4-year period, all pediatric patients presenting to the dermatology clinic with dorsal midline cutaneous stigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
(147 reference statements)
1
12
1
Order By: Relevance
“…Sardana et al. from India, reported spinal dysraphism in all nine patients with PWS present over the dorsal midline region . Isolated PWS is not considered as a marker for occult spinal dysraphism and is a more specific indicator when associated with other midline lumbosacral cutaneous lesions .…”
Section: Port‐wine Stain (Pws)mentioning
confidence: 97%
See 2 more Smart Citations
“…Sardana et al. from India, reported spinal dysraphism in all nine patients with PWS present over the dorsal midline region . Isolated PWS is not considered as a marker for occult spinal dysraphism and is a more specific indicator when associated with other midline lumbosacral cutaneous lesions .…”
Section: Port‐wine Stain (Pws)mentioning
confidence: 97%
“…Hemangiomas overlying the lumbosacral spine may be a marker for spinal dysraphism or may be associated with genitourinary abnormalities like imperforate anus, skeletal, and renal anomalies. Sardana et al found spinal dysraphism in four of five cases of hemangioma over the dorsal spine, and therefore MRI spine is advocated to look for underlying tethered cord or lipomeningocele (21). Hypothyroidism resulting from high levels of the enzyme 3-iodo thyronine deiodinase involved in the deactivation of thyroid hormone has been reported with large cutaneous or hepatic hemangiomas (22).…”
Section: Vasani Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous stigmata are found in 4.2% to 7.2% of all neonates. Although these cutaneous stigmata are frequently found in patients with CSD, the positive predictive value of these stigmata for the presence of CSD cannot be known without adequate large‐scale prospective studies . However, it is well accepted that a combination of two or more cutaneous stigmata has a high predictive value, and some stigmata have a higher risk than others (Fig.…”
Section: Spinal Dysraphismmentioning
confidence: 99%
“…In addition, there should be a high level of suspicion when cutaneous stigmata occur in combination with anogenital malformations or manifestations consistent with TCS. The common cutaneous stigmata are listed below and are categorized into proposed risk categories based on available data (Table ) .…”
Section: Spinal Dysraphismmentioning
confidence: 99%